Recent Progress on Perovskite-Based Electrocatalysts for Efficient CO2 Reduction - Tong Wu; Lihua Zhang; Yinbo Zhan; Yilin Dong; Zheng Tan; Bowei Zhou; Fei Wei; Dongliang Zhang; Xia Long (Molecules, 2023)
An efficient carbon dioxide reduction reaction (CO2RR), which reduces CO2 to low-carbon fuels and high-value chemicals, is a promising approach for realizing the goal of carbon neutrality, for which effective but low-cost catalysts are critically important. Recently, many inorganic perovskite-based materials with tunable chemical compositions have been applied in the electrochemical CO2RR, which exhibited advanced catalytic performance. Therefore, a timely review of this progress, which has not been reported to date, is imperative. Herein, the physicochemical characteristics, fabrication methods and applications of inorganic perovskites and their derivatives in electrochemical CO2RR are systematically reviewed, with emphasis on the structural evolution and product selectivity of these electrocatalysts. What is more, the current challenges and future directions of perovskite-based materials regarding efficient CO2RR are proposed, to shed light on the further development of this prospective research area.